The effectiveness of L2 pronunciation instruction: A critical systematic review of the intervention studies - Oktay Yağız; Fatma Kaya; Rabia Ötügen (Literacy Trek, 2024)
Pronunciation instruction studies have taken considerable attention in the field of foreign language teaching and research in recent years. For this systematic review, only the intervention studies indexed in SSCI were included. A literature search up to April 2024 was conducted using the Web of Science and relevant meta-analytic studies. Fifty-five interventions met the eligibility criteria based on the PRISMA 2020. This review is twofold: to examine the effects of English L2 pronunciation instruction and to identify the methodological status of these studies in terms of treatment formulation, design, sampling type/size, treatment duration, and outcome measures. Results showed that pronunciation instruction treatments positively affected L2 users' pronunciation performance. Regarding research methodology, the studies employed mostly pre- and post-tests, with at least one experimental group having relatively few delayed tests. The most common participant group was undergraduate students with pre-intermediate and intermediate levels. The participants' performance tended to be measured through technological tools in recent years. The suprasegmental features of speech that occurred with greater frequency compared to the mere segmental features. These studies also tended to include native speakers' ratings in the assessment phase of the instruction. The findings of this study are assumed to provide insights and recommendations for future research studies in L2 pronunciation.